Routine vs. on-demand analgesia in colonoscopy: a randomized clinical trial - Holme, Øyvind; de Lange, Thomas; Stallemo, Asbjørn; Wiig, Håvard; Hasund, Audun; Dvergsnes, Katrine; Garborg, Kjetil; Ystrøm, Carl Magnus; Løberg, Magnus; Hoff, Geir; Bretthauer, Michael; Kalager, Mette (Endoscopy, 2016)
Background and study aims: Colonoscopy is frequently performed with opioid analgesia, but the impact of drug delivery timing has not been studied in detail. Low-dose opioids administered before the procedure may provide better pain control than on-demand administration when the patient experiences pain. Patients and methods: A total of 119 outpatients were randomized to receive 50 μg of fentanyl either before colonoscopy (routine group) or on demand if needed during the colonoscopy (on-demand group). Additional fentanyl or midazolam was allowed in both groups if required. The primary outcome was pain measured on both a 100-mm visual analog scale (VAS; 0 = no pain, 100 = worst possible pain) and a four-point Likert scale (no, slight, moderate, or severe pain) immediately after the procedure.Results: A total of 61 patients in the routine group and 58 patients in the on-demand group were included in the study. Mean VAS pain scores were 27.4 mm in the routine group and 30.5 mm in the on-demand group (mean difference – 3.2 mm; 95 % confidence interval – 11.9 to 5.5; P = 0.5). On the Likert scale, moderate or severe pain was experienced by 25.0 % and 31.5 % of patients in the routine and on-demand groups, respectively (p = 0.5). Cecal intubation rate and time to reach the cecum were similar between the groups. More patients in the on-demand group (81.0 %) than in the routine group (62.3 %) were able to leave the clinic without the need for recovery time (P = 0.03).Conclusion: Routine administration of fentanyl did not provide better analgesia during colonoscopy than on-demand fentanyl, and more patients needed time for recovery.Trial registration: ClinicalTrials.gov (NCT01786434).